Colonial Waterbird Predation on Lost River and Shortnose Suckers in the Upper Klamath Basin. (1st November 2016) - Evans, Allen F.; Hewitt, David A.; Payton, Quinn; Cramer, Bradley M.; Collis, Ken; Roby, Daniel D.
Abstract: We evaluated predation on Lost River Suckers Deltistes luxatus and Shortnose Suckers Chasmistes brevirostris by American white pelicans Pelecanus erythrorhynchos and double-crested cormorants Phalacrocorax auritus nesting at mixed-species colonies in the Upper Klamath Basin of Oregon and California during 2009–2014. Predation was evaluated by recovering (detecting) PIT tags from tagged fish on bird colonies and calculating minimum predation rates, as the percentage of available suckers consumed, adjusted for PIT tag detection probabilities but not deposition probabilities (i.e., probability an egested tag was deposited on- or off-colony). Results indicate that impacts of avian predation varied by sucker species, age-class (adult, juvenile), bird colony location, and year, demonstrating dynamic predator–prey interactions. Tagged suckers ranging in size from 72 to 730 mm were susceptible to cormorant or pelican predation; all but the largest Lost River Suckers were susceptible to bird predation. Minimum predation rate estimates ranged annually from <0.1% to 4.6% of the available PIT-tagged Lost River Suckers and from <0.1% to 4.2% of the available Shortnose Suckers, and predation rates were consistently higher on suckers in Clear Lake Reservoir, California, than on suckers in Upper Klamath Lake, Oregon. There was evidence that bird predation on juvenile suckers (species unknown) in Upper Klamath Lake was higher than on adult suckers in Upper Klamath Lake, where minimum predation rates ranged annually from 5.7% to 8.4% of available juveniles. Results suggest that avian predation is a factor limiting the recovery of populations of Lost River and Shortnose suckers, particularly juvenile suckers in Upper Klamath Lake and adult suckers in Clear Lake Reservoir. Additional research is needed to measure predator-specific PIT tag deposition probabilities (which, based on other published studies, could increase predation rates presented herein by a factor of roughly 2.0) and to better understand biotic and abiotic factors that regulate sucker susceptibility to bird predation. Received January 19, 2016; accepted June 25, 2016 Published online October 7, 2016